Dash and Thud Activity Book - Ladybird Readers Starter Level 10 - Cunliffe,Ian (Ladybird, 2019)
This Activity Book accompanies the Reader. It provides practice of key language structures and vocabulary, while developing a range of skills: singing, spelling and writing, reading, speaking, and listening. Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language. Recommended for children aged 4+, the eight levels of Readers and six levels of Activity Books follow the CEFR framework (Pre-A1 to A2+) and include language activities that help develop key skills and provide preparation for the Cambridge English: Young Learners (YLE) Starters, Movers and Flyers exams. The Starter level introduces phonics and sight words. Each book contains two versions of the story: the first with single words focusing on phonics, and the second with full sentences introducing sight words. It is Pre-A1 in the CEFR framework.